The Community-Based Monitoring System of Philippine Statistics Authori-ty in North Cotabato: Basis for A Pre-Deployment Training Program - Cagasan, Kareen Calibayan (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study provides a comprehensive review and analysis of the vital role of enumerators in the Community-Based Monitoring Sys-tem (CBMS) in North Cotabato, Philippines. The research aims to shed light on the responsibilities, challenges, and impacts faced by enumerators during the data collection process, as well as to pro-pose evidence-based strategies for improving their performance and the accuracy of data collection. The CBMS is a crucial system for collecting disaggregated data necessary for evidence-based decision-making and targeted development programs. However, there needs to be more literature regarding the specific challenges and roles of enumerators in ensuring the accuracy and integrity of the monitoring process. By addressing this gap, this study strives to enhance the effectiveness and reliability of the CBMS. Drawing from international, national, and local contexts, this research pro-vides insights into the importance of enumerators' roles based on experiences from other countries implementing similar systems. It discusses the potential biases and errors enumerators may en-counter during data collection. It emphasizes the need for commu-nity collaboration and support to ensure the accuracy and com-prehensiveness of the collected data. Furthermore, the study high-lights the significance of understanding enumerators' roles in identifying poverty hotspots, tracking changes in poverty levels, and devising targeted interventions to address the root causes of poverty. By bridging the gap in the literature, this research aims to contribute to a better understanding of the enumerator's role and offer valuable insights for future research and the development of strategies and training programs to improve the CBMS.